2004
DOI: 10.1016/s0002-9440(10)63142-2
|View full text |Cite
|
Sign up to set email alerts
|

A Peroxisome Proliferator-Activated Receptor-α Activator Induces Renal CYP2C23 Activity and Protects from Angiotensin II-Induced Renal Injury

Abstract: Cytochrome P450 (CYP)-dependent arachidonic acid (AA) metabolites are involved in the regulation of renal vascular tone and salt excretion. The epoxygenation product 11,12-epoxyeicosatrienoic acid (EET) is anti-inflammatory and inhibits nuclear factor-kappa B activation. We tested the hypothesis that the peroxisome proliferator-activated receptor-alpha-activator fenofibrate (Feno) induces CYP isoforms, AA hydroxylation, and epoxygenation activity, and protects against inflammatory organ damage. Double-transgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(101 citation statements)
references
References 45 publications
6
94
1
Order By: Relevance
“…However, the further analysis in intact proximal tubules revealed that Ang II failed to activate ERK in the presence of arachidonic acid or 5,6-EET, supporting the negative effect of arachidonic acid metabolites on the ERK pathway (Li, Y and Seki G, unpublished observation). Moreover, the negative effect of EET on ERK activation is consistent with a protective role of EET in Ang II-induced renal injury [71]. In this model, AT 1 mediates both stimulatory and inhibitory effects of Ang II.…”
Section: Roles Of Arachidonic Acid Metabolites In Ang II Actionssupporting
confidence: 80%
See 1 more Smart Citation
“…However, the further analysis in intact proximal tubules revealed that Ang II failed to activate ERK in the presence of arachidonic acid or 5,6-EET, supporting the negative effect of arachidonic acid metabolites on the ERK pathway (Li, Y and Seki G, unpublished observation). Moreover, the negative effect of EET on ERK activation is consistent with a protective role of EET in Ang II-induced renal injury [71]. In this model, AT 1 mediates both stimulatory and inhibitory effects of Ang II.…”
Section: Roles Of Arachidonic Acid Metabolites In Ang II Actionssupporting
confidence: 80%
“…It is tempting to speculate, however, that renal proximal tubules may have to develop the unique mechanism to attenuate excessive actions of Ang II. Indeed, in situ proximal tubular fluid is reported to contain markedly high concentrations of Ang II [44], and uncontrolled Ang II actions may result in unwarranted sequences such as cell hypertrophy or cell damage [14,71].…”
Section: Roles Of Arachidonic Acid Metabolites In Ang II Actionsmentioning
confidence: 99%
“…PPAR-␣ activation has been shown to induce renal CYP2C23 activity under pathological and nonpathological conditions. 32,33 Contrary to the effects of A-192621 treatment on CYP4A expression in rats on high salt, chronic ET B blockade did not change CYP2C23 protein expression. Furthermore, clofibrate administration did not influence CYP2C23 expression in A-192621-treated rats on a high-salt diet.…”
Section: Discussionmentioning
confidence: 87%
“…Since the effect of clofibrate is limited to saline treated rats, which are likely producing more EDHF in response to ACh, we believe that clofibrate potentiates EDHF. Clofibrate and other fibrates are peroxisome proliferator activated receptor-(PPAR ) agonists and have been shown to induce CYP 2C23 22 and increase epoxyeicosatrienoic acid production in the kidney. 23 Furthermore, in vitro studies revealed that incubation of endothelial cells with clofibrate for 72 hours causes membrane hyperpolarization, an effect attributed to EET formation.…”
Section: Sankaralingam Et Al Clofibrate Prevents Endothelial Dysfuncmentioning
confidence: 99%